Efficacy of 8-week oral iron supplementation on fatigue and physical capacity in young women with iron deficiency anemia: An uncontrolled pilot clinical trial - Mohamed Achraf Harrabi; Thouraya Fendri; Fatma Chaari; Rahma Ayed; Atyh Hadadi; Wissal Boughattas; Ines Mezghani; Choumous Kallel; Haithem Rebai; Mouna Turki; Fatma Ayadi; Sonia Sahli (PLoS ONE, 2025)
This study aims to investigate the effect of 8 weeks of ferrous sulfate supplementation (160 mg elemental iron/day) on fatigue and physical performance in young women with iron deficiency anemia (IDA). In this uncontrolled pilot clinical trial, twenty-three women with IDA aged between 18 and 30 years participated in this study. Aerobic fitness, muscle strength and muscle endurance were performed to evaluate physical capacities. Moreover, the multidimensional fatigue inventory (MFI-20) was used to assess general, physical, and mental fatigue, reduced activity and motivation. Due to multiple comparisons, the level of significance was set at 0.00625. The results of this study revealed that muscle endurance values increased significantly (P < 0.001) after 8 weeks of iron supplementation compared to pre-intervention values. In addition, scores of general (P < 0.001), physical (P < 0.001) and mental (P < 0.001) fatigue, and reduced activity (P < 0.001) and motivation (P = 0.006) decreased significantly in post- intervention compared to pre- intervention. However, there were no improvements in aerobic fitness (P = 0.008) and muscle strength (P = 0.086). In women of reproductive age with IDA, 8 weeks of iron supplementation improve muscle endurance, but not aerobic fitness or muscle strength. These improvements could be explained by the increase in hemoglobin (Hb) (by 17.62%) and serum ferritin (by 63.2%) concentrations and the decrease in fatigue scores after the supplementation period.